The emesine assassin bug genus Empicoris (Hemiptera: Heteroptera: Reduviidae) from Vietnam, with descriptions of two new species - Ishikawa, Tadashi; Truong, Xuan Lam; Okajima, Shûji (Zootaxa, 2012)
Five species of the reduviid genus Empicoris are recognized in Vietnam, including a previously recorded species E. ru-bromaculatus (Blackburn). Two species, E. montanus sp. n. and E. laocaiensis sp. n., are newly described. Empicorisminutus Usinger and E. tesselatoides Wygodzinsky et Usinger are recorded from Vietnam for the first time. A key to the species of Vietnamese Empicoris is presented.